Feature : When supercomputers go over to the dark side. (21st March 2017) - White, Martin; Scott, Pat
Abstract: Despite oodles of data and plenty of theories, we still don't know what dark matter is. Martin White and Pat Scott describe how a new software tool called GAMBIT – run on supercomputers such as Prometheus – will test how novel theories stack up when confronted with real data.